Pengembangan Materi Tes Keterampilan Menyimak Bahasa Arab Menggunakan Moodle Untuk Meningkatkan Kemampuan Menyimak Mahasiswa Universitas Darussalam Gontor - Moh. Ismail; Aufa Alfian Musthafa (At-Ta'dib, 2018)
Listening skills (maharah al-istima ') is one of the fundamental skills that must be mastered by anyone who learns Arabic. Listening skills in Arabic need to be improved through structured and systematic efforts. The objective of listening skills is to increase the sensitivity of students in listening to the phrase (al-kalam) in Arabic and to understand the meaning of the expression. One of the universities that has great attention in developing product of listening skills is University of Darussalam Gontor.  The objectives of this study are (1) To develop the material of online Arabic Language Test using Moodle software to improve the Arabic listening skill of UNIDA students, (2) To find out the right method for implementing the online Arabic tests using Moodle software to improve the Arabic listening skill of UNIDA students. This study used research and development method. This method is a form of qualitative and quantitative approaches. In the sampling technique, researchers used the Proportionate Stratified Random Sampling technique. Data collection techniques used pre-test & post-test, observation, interviews, questionnaires. The data analysis technique used data analysis techniques such as the type of Embedded Mixed Methods with the calculation formula related t-test using SPSS 17.0 software. The results of this study are (1) Products in the form of full text and audio question banks to improve Arabic listening skills that can be accessed through https://alikhtibar.com. The question bank product which is designed consists of 5 levels namely Level 1 (Beginner), Level 2 (Elementary), Level 3 (Intermediate), Level 4 (Upper Intermediate), Level 5 (Advance). (2) Based on the results of data analysis, it was found that the products that had been developed are able to improve the Arabic listening ability of UNIDA students.